Dinamika Pelajar SMA dan SMK Pelaku Vandalisme di Kota Yogyakarta - Andhy Surya Hapsara (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
This study discusses about the factors which affect their interest backgrounds and motifs, the opportunities and the obstacles of vandalism as well as solutions to solve the problem of vandalism. This study used qualitative descriptive reseach as an approach. The data collection was done through three techniques namely observation, interview, and documentation studies. The result of this study revealed that; (1) vandalism is an action as an interaction form with other groups mediated by the use of individual or gang initial symbols as cultural attack. (2) Vandalism is influenced by various factors such as family, social environment, school and their perception about vandalism. (3) The background of vandalism is due to emotional attachments with their peer group. (4) The vandalish get some opportunities by performing vandalism like respect and status/recognition from their peer group. (5) Some solutions to overcome the problems are carrying out the